The Influence of Instagram Analogue Surabaya on the Interest of Analogue Camera Followers - Adam Zakaria; Moch. Subechi Nurcahyo (DIGICOM : Jurnal Komunikasi dan Media, 2023)
This study aims to determine the effect of the Instagram account @analog surabaya on interest in photography using analogue cameras on followers. The theory used is the theory of uses and gratification. This theory explains the nature of audiences who are active in consuming media so that they can be selective in sorting out media messages that aim to meet audience needs. The method used in this research is quantitative method. By using a questionnaire in drawing data conclusions. The sampling technique in this study used simple random sampling. Based on the research that has been done, the researcher draws the conclusion that there is an influence of the Instagram account @analog surabaya on interest in photography using analogue cameras on followers. The correlation coefficient is 0.713 with a tendency of influence of 22.7%. The needs of the audience in this study are literacy needs about photography, especially analogue cameras, which are influenced by the @analog Surabaya Instagram account by 22.7%.